Direct combustion of waste oil in domestic stove by an internal heat re-circulation atomization technology: Emission and performance analysis. (1st March 2020) - Zhao, Nan; Li, Bowen; Chen, Deying; Ahmad, Riaz; Zhu, Yingdan; Li, Gang; Yu, Zhengping; Li, Jinghao; Wang, Enlu; Yun, Seongwan; Yoon, Hyukjin; Yoon, Inseok; et al.
Highlights: Develop an internal heat re-circulation and self-atomization burner was developed. Direct combustion of three waste oils in a self-atomized turbulence burning stove. Quantify the emission factors, thermal efficiency and improved combustion efficiency. Compare the performances of waste oils with traditional fuel/stove combinations. Rate the emission of stove fueled with waste oil by current available standards. Abstract: Direct use of waste oil as fuel to meet the residential energy demands, is very attractive due to its potentials to decrease fossil fuel consumption, reduce pollution and increase sustainability. This paper uses a domestic stove with an internal heat re-circulation and self-atomization technology to burn yellow waste cooking oil (WCO-1), brown waste cooking oil (WCO-2) and waste lubricant oil (WLO). Emission factors (EFs), energy efficiency and modified combustion efficiency (MCE) of this combined fuel/stove system were determined under space-heating and cooking modes. The results showed that EFs of CO, PM2.5, total 16 PAHs and corresponding toxic equivalent quantity (TEQ) values ranged from 2.18 × 10 3 to 4.90 × 10 3 mg/MJ net, 16.36–69.40 mg/MJ net, 2.39–12.93 μg/MJ net and 0.16–0.92 μg of TEQ/MJ net . WCO-1 was verified to be the cleanest fuel with the highest energy efficiency (85.3 ± 3.3% and 90.4 ± 2.2%) and lowest emission levels, such as NO (53.75 ± 2.62 and 37.09 ± 5.41 mg/MJnet ), NO2 (82.40 ± 3.96 and 56.87 ± 8.29 mg/MJnet ) and PM2.5 (20.94 ± 6.55 and 16.35 ± 5.06 mg/MJnet ) compared to WCO-2 and WLO. The estimated total cost of using waste oil for each household in winter was much cheaper than some current available clean energy means, including only USD 400 of stove price and USD 250/ton of fuel per year. It is a promising candidate choice for replacing low-quality solid fuels in rural China and 2.62 million rural households would achieve environmental and economic benefits if promoting direct combustion of waste oil for daily heating and cooking.